2017
DOI: 10.1097/md.0000000000008816
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of lung cancer with menstrual and reproductive factors may be influenced by passive smoking, cooking oil fumes, and tea intake

Abstract: The aim of this study was to investigate the association of menstrual and reproductive factors with risk of lung cancer in women. Potential etiological clues related to lung cancer in women are identified to inform preventive strategies.Case–control study of 477 newly diagnosed women with lung cancer and 479 age-matched (±2 years) controls. Data on menstrual and reproductive factors and history of oral contraceptive use were obtained on personal interviews using a structured questionnaire. Risk factors were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
4
19
2
Order By: Relevance
“…In our JFC Study, a menarche age greater than 18 years old could be a marker of poor childhood nutritional status, which has long-term adverse influence on health [23], [43], [44]. This increased risk by later menarche was also found in six other studies conducted among Chinese women [23], [25], [27], [45], [46], [47] although there was one study with potentially decreased risk linked to late menarche [22].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In our JFC Study, a menarche age greater than 18 years old could be a marker of poor childhood nutritional status, which has long-term adverse influence on health [23], [43], [44]. This increased risk by later menarche was also found in six other studies conducted among Chinese women [23], [25], [27], [45], [46], [47] although there was one study with potentially decreased risk linked to late menarche [22].…”
Section: Discussionsupporting
confidence: 60%
“…Among these patients with known histology information, 65% of the NSCLC cases were adenocarcinoma. Among other studies conducted in China, lung cancer histology was largely dominated by adenocarcinoma, accounting for 61% to 73% of all female lung cancer diagnoses [22], [51]. East Asian patients show a much higher prevalence of epidermal growth factor receptor (EGFR) mutations, compared with Caucasian patients with NSCLC (approximately 30% vs. 7%, predominantly among patients with adenocarcinoma and never-smokers), thus showing a higher proportion of patients who are responsive to EGFR tyrosine kinase inhibitors (EGFR-TKIs) [28], [52].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We further found that exposure to cooking oil fumes and to a new-built or newly renovated home in the past year were associated with an increased risk of overdiagnosed COPD. Previous studies reported that cooking oil fumes without cigarette smoking were associated with pulmonary disease, particularly lung cancer, 30,31 which indicates the negative effect of cooking oil fumes on the lungs. Similarly, indoor air pollutants from building materials in a new-built or newly renovated home, mainly formalin and volatile organic compounds, were associated with an increased risk of COPD.…”
Section: Discussionmentioning
confidence: 99%